The effect of foottype and laterality on ankle sprain in elite female volleyball players - Vareka, I.; Varekova, R.; Lehnert, M.; Kolar, P.; Stejskal, D. (Kinesiology, 2009)
Volleyball is a team game with a high incidence of ankle sprain. The purpose of our research was to investigate the ankle sprain history and incidence in elite female volleyball athletes according to the Root functional foot type and laterality. The additional aims were to investigate the foot type prevalence and the effect of age on ankle sprain incidence. Sixty-two elite female volleyball athletes (17-25 years, mean=20.7, SD=2.03) were investigated by an experienced rehabilitation physician for functional foot type according to Root, while the personal history of ankle sprain and laterality were estimated based on asking questions. The obtained data of ankle sprain cases in the subjects did not have the normal distribution (Kolmogorov-Smirnov, d=.26, p<.01). Also, the Spearman correlation and the Wilcoxon and Kruskall-Wallis tests were used to find out the significance of each case. Almost 68% of the subjects had a history of ankle sprain (1-13 cases per person, 2 cases on average). Ankle sprain has been confirmed as a very common injury in volleyball athletes. Spearman`s correlation did not show the significance of age (Spearman`s correlation, r1=-.1873; p<.05) in spite of the exclusion of three subjects with extremely high ankle sprain incidence (ASI) (r2=-.1656; p<.05). Laterality was not significant, either. (Wilcoxon test, p=.07). The findings supported previously described differences in the prevalence of various functional foot types - compensated rearfoot varus and flexible forefoot valgus were the most common ones (56.6% and 27.4%, respectively), compensated forefoot varus, rigid forefoot valgus and neutral foot were relatively rare (8.1%, 4.8% and 3.3%, respectively). Subjects with the two most common foot types had an obviously higher average incidence of ankle sprain (2.4 and 2.0, respectively) than the other ones (.8, .7 and .5, respectively), but without significance (Kruskall-Wallis, p=.44). The non-significance of foot type effect on ankle sprain frequency was questionable due to the very low prevalence or lack of other functional foot types with known empirical evidence of increased ankle sprain risk.